Information and Communication Technology as a Veritable Tool for Administrators in University: From Teaching Perspectives to Challenge in Education - Bolaji, Hammed Olalekan; Ajape, Rasheedat Oladunni (Universitas Pendidikan Indonesia (UPI), 2022)
Information and communication technology (ICT) plays a critical role in improving educational quality. Because of its strengths in facilitating administration operations such as data storage, knowledge management, and decision-making, ICT solutions for administration and management are currently popular in universities. Here, to support teaching and learning processes as well as to achieve the veritable tools for administrators in private universities, the purpose of this study was to gain a better understanding of how ICT applications are used, the tools used by the school administrator, and the efficacy of ICT applications for administrative and managerial tasks at universities. It is obvious that lack of commitment by Administrators; lack of ICT strategy; lack of competent staff to manage the ICTs and low skill level of the administrators led to the reasons for poor use of the ICTs in Universities. Other reasons that added to the underuse of the ICTs are insufficient budget and irregular power supply. This paper presents a survey of the literature on ICT applications and their efficacy in university administration functions. The findings provided insight into how administrators might improve and expand their use of ICT in daily administrative duties to make their work more efficient and effective. Finally, recommendations for university administrations to improve their ICT understanding and practice will be explored.